Tool life and wear mechanisms during Alloy 625 face milling. Issue 5 (July 2016) - Rodrigues, Marcelo; Hassui, Amauri; Lopes da Silva, Rodrigo; Loureiro, Daniel
Abstract Nickel-based alloys, particularly Alloy 625, are very important materials which have been increasingly used in applications that require wear resistance, particularly in the oil and gas industries. One of their characteristics is low machinability, which is due to their combined properties of high-temperature hardness, mechanical strength, and corrosion and wear resistance. These properties mean that low cutting speeds are needed in order to increase tool life, although this is not always achieved. The main goal of this work is to evaluate different cemented carbide grades, cutting speeds, and feed per tooth rates, aiming to determine the best condition for face milling of nickel-based 625 superalloy. The tool life performance of the cutting tools and the wear mechanisms were analyzed based on the results of milling tests using a cutter with cemented carbide inserts. The main results indicate that tool wear mechanisms in the Alloy 625 milling are similar to those that occur in other nickel-based superalloys, such as 718 and 713. However, the wear rate is lower and there is evidence of occurrence of oxidation wear.